Towards sustainable tourism in Jamaica. - BOXHILL, Ian (1995)
Discusses the need for a careful assessment of the socio-economic and environmental impact of the growth of tourism in Jamaica. Suggests fundamental changes which must be made if tourism is to become sustainable in Jamaica.